Fantasies of Salvation : Democracy, Nationalism, and Myth in Post-Communist Europe - Tismaneanu, Vladimir (Book collections on Project MUSE., 1998)
Eastern Europe has become an ideological battleground since the collapse of the Soviet Union, with liberals and authoritarians struggling to seize the ground lost by Marxism. In Fantasies of Salvation, Vladimir Tismaneanu traces the intellectual history of this struggle and warns that authoritarian nationalists pose a serious threat to democratic forces. A leading observer of the often baffling world of post-Communist Europe, Tismaneanu shows that extreme nationalistic and authoritarian thought has been influential in Eastern Europe for much of this century, while liberalism has only shallow.